Aligned bacterial PHBV nanofibrous conduit for peripheral nerve regeneration. (August 2015) - Demirbilek, Murat; Sakar, Mustafa; Karahaliloğlu, Zeynep; Erdal, Ebru; Yalçın, Eda; Bozkurt, Gökhan; Korkusuz, Petek; Bilgiç, Elif; Temuçin, Çağrı Mesut; Denkbaş, Emir Baki
Abstract The conventional method of peripheral nerve gap treatment is autografting. This method is limited. In this study, an aligned nanofibrous graft was formed using microbial polyester, Poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV). The regenerative effect of the graft was compared with that of autografting in vivo. To determine the regenerative effect, rats were assessed with sciatic nerve functional index, electromyographic evaluation, and histological evaluation. Results found in this study include PHBV grafts stimulated progressive nerve regeneration, although regeneration was not comparable with that of autografting. We conclude that the study results were promising for aligned bacterial polymeric grafts for peripheral nerve regeneration.